1996
DOI: 10.1080/01431169608948716
|View full text |Cite
|
Sign up to set email alerts
|

Satellite thermal survey—a new tool for the study of seismoactive regions

Abstract: The National Oceanic and Atmospheric Administration (NOAA)-series satellite thermal images(STI) study showed the presenceof positive anomalies of the outgoing Earth radiation flux recorded at night time and associated with largest linear structures and fault systems of the crust. The analysis of a continuous series (100-250 days) of nightly STl data for a period of 10 years allowed identification of a set of IR radiation anomalies in the Central Asian seismoactive region, Iran, Egypt, etc. About 10000 NOAA ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 5 publications
1
115
1
Order By: Relevance
“…NCEP-FNL data shows a maximum temperature difference of 7 ºC in the epicenter grid. Compared with the 4-5 ºC temperature difference background, the increase caused by the earthquakes is around 2-3 ºC, which is similar to the value reported by Tronin (1996) and Saraf and Choudhury (2004). The NCEP data anomaly also corresponds well to the epicenter location, and this could provide a method to estimate the future epicenter.…”
Section: Discussionsupporting
confidence: 83%
“…NCEP-FNL data shows a maximum temperature difference of 7 ºC in the epicenter grid. Compared with the 4-5 ºC temperature difference background, the increase caused by the earthquakes is around 2-3 ºC, which is similar to the value reported by Tronin (1996) and Saraf and Choudhury (2004). The NCEP data anomaly also corresponds well to the epicenter location, and this could provide a method to estimate the future epicenter.…”
Section: Discussionsupporting
confidence: 83%
“…RST was applied for the first time to seismically active areas monitoring, in the case of the disastrous 1980 Irpinia-Basilicata earthquake (Di Bello et al, 2004;Tramutoli et al, 2001b), then it was successfully tested in several cases: Athens, 7 September 1999 ; Izmit, 17 August 1999 ; Gujarat, 26 January 2001 (Genzano et al, 2007), Boumerdes/Thenia, 21 May 2003(Aliano et al, 2007; Hector Mine, 16 October 1999(Aliano et al, 2008a, Umbria-Marche, October 1997 (Aliano et al, 2008b), Mestia Tianeti (Georgia), 23 October 1992 , and various low magnitude events occurred in Greece and Turkey, May and June 1995-1996(Corrado et al, 2005.…”
Section: A Robust Estimator Of Thermal Anomaliesmentioning
confidence: 99%
“…Several studies (see for example Gorny et al, 1988;Qiang and Dian, 1992;Tronin, 1996;Qiang et al, 1997;Tronin et al, 2002;Ouzounov and Freund, 2004) have been performed, in the past years, reporting the appearance of spacetime anomalies in TIR satellite imagery, from weeks to days, before severe earthquakes. Different authors (Qiang et al, 1991;Tramutoli et al, , 2009, in order to explain the appearance of anomalously high TIR records near the place and the time of earthquake occurrence, attributed their appearance to the increase of green-house gas (such as CO 2 , CH 4 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (see, for example, Qiang Zu-ji and Dian Chang-Gong, 1992;Qiang et al, 1991Qiang et al, , 1997Tronin, 1996Tronin, , 2000Tronin et al, 2002) have claimed a possible correlation between TIR 1 satellite anomalies, observed from months to weeks before an earthquake, and the occurrence of the seismic event itself. Such a claimed correlation has been considered, up to now, with some caution by scientific community mainly for the insufficiency of the validation data-sets and the scarce importance attached by those authors to other causes (e.g.…”
Section: Introductionmentioning
confidence: 99%